Mapping the field of Islamic banking and finance education: A bibliometric analysis and future research agenda - Rofiul Wahyudi; Lina Handayani; Zalik Nuryana; Riduwan Riduwan (Journal of Education and Learning (EduLearn), 2023)
This article examined trends in Islamic education and finance publications using bibliometric analysis. The authors used co-citation and co-word analysis to examine 449 Islamic education and finance studies from Scopus database. In the co-citation analysis, 10 themes in Islamic education and finance were identified. After that, co-word analysis is used to understand and identify each research theme’s potential future research directions. The results showed that per year the average publication of articles was 2.65. There has been extensive research on this topic in the United States (US) and the United Kingdom (UK), and the most popped-up keywords are ‘education’, ‘finance education’, ‘banking education’ and very limited ‘Islamic finance education’. Further research can be developed using Islamic jurisprudence education, Islamic insurance education, Islamic capital market education, zakat education and waqf as keywords. In addition, the study offers a visualization map of theme patterns for future studies to create educational fields for Islamic banking and finance education, particularly in Muslim-majority nations like Indonesia, Malaysia, and the Middle East. This research contributes as a foundation for further research in enriching and developing knowledge about Islamic education and finance, especially in majority countries.